2020
DOI: 10.1371/journal.ppat.1008812
|View full text |Cite
|
Sign up to set email alerts
|

A role for gorilla APOBEC3G in shaping lentivirus evolution including transmission to humans

Abstract: The APOBEC3 deaminases are potent inhibitors of virus replication and barriers to crossspecies transmission. For simian immunodeficiency virus (SIV) to transmit to a new primate host, as happened multiple times to seed the ongoing HIV-1 epidemic, the viral infectivity factor (Vif) must be capable of neutralizing the APOBEC3 enzymes of the new host. Although much is known about current interactions of HIV-1 Vif and human APOBEC3s, the evolutionary changes in SIV Vif required for transmission from chimpanzees to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…Cellular restriction factors and their antagonization by viral effector proteins can act as decisive factors for cross-species transmission of viruses. This has extensively been studied for antiretroviral restriction factors like APOBEC3 deaminases which need to be degraded by adapted lentiviral vif proteins in order to allow cross-species infection [ 47 ]. In contrast, the mechanisms limiting cross-species infection of cytomegaloviruses are less well understood.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular restriction factors and their antagonization by viral effector proteins can act as decisive factors for cross-species transmission of viruses. This has extensively been studied for antiretroviral restriction factors like APOBEC3 deaminases which need to be degraded by adapted lentiviral vif proteins in order to allow cross-species infection [ 47 ]. In contrast, the mechanisms limiting cross-species infection of cytomegaloviruses are less well understood.…”
Section: Discussionmentioning
confidence: 99%
“…This observation suggests that gorilla APOBEC3G has played a role in restricting the cross-species transmission of SIVcpz from chimpanzees to gorillas as a species barrier and that SIVcpz Vif evolved into SIVgor Vif by acquiring the ability to counteract gorilla APOBEC3G. Intriguingly, Nakano et al recently demonstrated that a single amino acid mutation (M16E) enabled SIVcpz Vif to degrade and counteract gorilla APOBEC3G [ 50 ]. Methionine (M) at amino acid position 16 is highly conserved in SIVcpz Vif, while glutamic acid (E) is conserved in SIVgor Vif [ 50 ].…”
Section: Role Of Mammalian Apobec3 Proteins In Cross-species Lentimentioning
confidence: 99%
“…Intriguingly, Nakano et al recently demonstrated that a single amino acid mutation (M16E) enabled SIVcpz Vif to degrade and counteract gorilla APOBEC3G [ 50 ]. Methionine (M) at amino acid position 16 is highly conserved in SIVcpz Vif, while glutamic acid (E) is conserved in SIVgor Vif [ 50 ]. Second, SIVcpz Vif proteins cannot counteract human antiviral APOBEC3H, while HIV-1M Vif can [ 51 ].…”
Section: Role Of Mammalian Apobec3 Proteins In Cross-species Lentimentioning
confidence: 99%
“…APOBEC3 proteins are examples of host factors that restrict cross-species transmission of lentiviruses [reviewed by Nakano et al (2017a) ; Uriu et al (2021) ]. Interactions between mammalian A3 proteins and lentiviral Vifs are largely specific to viruses in their hosts ( Mariani et al, 2003 ; Compton et al, 2012 ; Etienne et al, 2015 ; Yamada et al, 2016 ; Zhang et al, 2016 ; Nakano et al, 2020 ). As examples, HIV-1 Vif can degrade A3G protein from humans but not from African green monkeys or rhesus macaques ( Bogerd et al, 2004 ; Schrofelbauer et al, 2004 ; Xu et al, 2004 ).…”
Section: Potential Utilization Of Vif-resistant A3 Proteins For An Hiv-1 Functional Curementioning
confidence: 99%